Human capital and life satisfaction in economic transition: Econometric evidence from pre‐ and post‐Arab Spring Egypt1. Issue 2 (26th December 2016) - Silver, Hannah C.; Caudill, Steven B.; Mixon, Franklin G.
Abstract: This study explores the life satisfaction of Egyptians – with a particular focus on the impact of higher education on happiness – both before and after that country's Arab Spring of 2011. Ordered logit results point to positive and significant relationships between life satisfaction and both perceived high incomes and the human capital variable, good health, for the pre‐ and post‐Arab Spring periods in Egypt, thus confirming prior studies of transition economies. For a second human capital variable – secondary education – the results indicate a positive and significant relationship with happiness in pre‐Arab Spring Egypt, while that relationship for post‐Arab Spring Egypt is negative and significant. This particular finding is probably the result of the failure of educated Egyptians to achieve a better life despite their investments in human capital – due to the lack of opportunity that accompanied the failure of the country's Arab Spring to change the political and social environment.